Vemurafenib reverses immunosuppression by myeloid derived suppressor cells. Issue 7 (13th April 2013) - Schilling, Bastian; Sucker, Antje; Griewank, Klaus; Zhao, Fang; Weide, Benjamin; Görgens, André; Giebel, Bernd; Schadendorf, Dirk; Paschen, Annette
Abstract : Myeloid derived suppressor cells (MDSCs) suppress innate and adaptive immunity, thereby limiting anti‐tumor immune responses in cancer patients. In patients with advanced melanoma, the phenotype and function of MDSCs remains controversial. In our study, we further explored two distinct subpopulations of MDSCs and investigated the impact of Vemurafenib on these cells. Flow cytometry analysis revealed that in comparison to healthy donors and patients with localized disease, PBMCs from patients with metastatic melanoma showed an increased frequency of CD14 + HLA‐DR −/low monocytic MDSCs (moMDSCs) and of a previously unrecognized population of CD14 − CD66b + Arginase1 + granulocytic MDSCs (grMDSCs). In vitro, both populations suppressed autologous T‐cell proliferation, which was tested in CFSE‐based proliferation assays. Vemurafenib treatment of melanoma patients reduced the frequency of both moMDSCs and grMDSCs. According to our in vivo finding, conditioned medium (CM) from Vemurafenib treated melanoma cells was less active in inducing moMDSCs in vitro than CM from untreated melanoma cells. In conclusion, patients with advanced melanoma show increased levels of moMDSCs, and of a population of CD14 − CD66b + Arginase1 + grMDSCs. Both MDSCs are distinct populations capable of suppressing autologous T‐cell responses independently of each other. In vitro as well as in vivo, Vemurafenib inhibits the generation of human moMDSCs. Thus, Vemurafenib decreases immunosuppression in patients with advanced melanoma, indicating its potential as part of future immunotherapies. Abstract : What's new? Censoring of the immune system, leading to its inability to mount an effective attack against tumor cells, is suspected to contribute to the advance of melanoma. The restrained response may be the result of two distinct populations of myeloid derived suppressor cells (MDSCs), as reported here. Monocytic MDSCs and a population of previously unrecognized Arginase1 + granulocytic MDSCs were detected at elevated frequencies in patients with metastatic melanoma. Frequencies of both subtypes declined in patients with clinical response to the enzyme inhibitor vemurafenib, which was further found to block in vitro generation of monocytic MDSCs.